Copy-cat evolution: Divergence and convergence within and between cat and dog breeds - Abby Grace Drake; Liam J. Revell; Christian Peter Klingenberg; Jimmy C. Lattimer; Nathan C. Nelson; Martin J. Schmidt; Allison L. Zwingenberger; Joshua K. Moyer; Jonathan B. Losos (Proceedings of the National Academy of Sciences, 2025)
Many domesticated species exhibit remarkable phenotypic diversity. In nature, selection produces not only divergence but also convergence when organisms experience similar selective pressures. Whether artificial selection during domestication also produces convergence has received little attention. Three-dimensional shape analysis of domestic cat and dog skulls demonstrated convergence at multiple levels. Most broadly, cats and dogs have both diversified greatly: equaling or exceeding the morphological disparity among all modern-day species of their respective families. Moreover, as a result of artificial selection, some breeds of these two phenotypically distinct species, evolutionarily separated for 50 My, have converged to such an extreme extent that they are more similar to each other than they are to many members of their own species or their ancestors, a phenomenon never previously observed in domesticated species. Remarkably, this convergence evolved not only between dogs and cats but also multiple times within each taxon.